Aktualisasi Peran Dakwah Mahasiswa dalam Membangun Masyarakat Islami: Pengabdian - Yogi Muhammad Saputro; Fadhia Ananda; Oscharil Aji Mukti; Triono Ali Mustofa; Muhammad Wildan Shohib; Muh. Nur Rochim Maksum (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aimed to actualize the role of university students in Islamic preaching (dakwah) to empower rural communities with limited access to religious education. The activity was conducted in Gerdu Village, Karangpandan Sub-district, Karanganyar Regency, Central Java, using a qualitative approach and the Participatory Action Research (PAR) method. This method allowed students and community members to be actively involved in identifying religious issues, designing solutions, and collaboratively implementing sustainable programs. Data were collected through participatory observation, in-depth interviews, and documentation. The program consisted of various Islamic educational activities such as children’s Quran classes (TPA), women’s religious studies, Quran recitation improvement (tahsin), Islamic storytelling, educational outbound games, and health counseling. The results showed increased community participation in religious activities and the emergence of collective awareness to uphold Islamic values in daily life. The students also gained valuable hands-on experience in delivering contextual and applicable religious guidance. These findings indicate that the participatory community-based dakwah model is effective in rural settings and can be replicated in other areas with similar social characteristics.